Penerapan Judicial Pardon di Belanda dan Indonesia: Analisis Komparatif terhadap Rechtelijk Pardon pada KUHP Baru di Indonesia - Cantika Qori Nirmalasari; Muhammad Azil Maskur (IAIN Langsa, 2026)
This study aims to comparatively analyze the normative construction, requirements for application, and implementation challenges of rechterlijk pardon in the Netherlands and Indonesia within the civil law system. The focus of the study is directed at comparing Article 9a of the Dutch Wetboek van Strafrecht and Article 54 paragraph (2) of Law Number 1 of 2023 on the Indonesian Criminal Code (KUHP), as well as identifying the objective parameters developed through the jurisprudence of the Hoge Raad. This article constitutes a qualitative library-based research. The methodology employed is normative juridical research with comparative, conceptual, and philosophical approaches. The findings indicate that the Netherlands has consistently implemented rechterlijk pardon through strict cumulative requirements and measurable objective parameters. In contrast, the regulation of judicial pardon under the 2023 Criminal Code remains general and ambiguous, and lacks technical guidelines, thereby potentially creating legal uncertainty and the risk of abuse of power.